Wetlands management in Vietnam : (Worldfish center, 2003)
This volume compiles and presents side by side the perspectives of many of the researchers and offcials at national and provincial levels who are at the forefront of addressing these questions. It includes reviews of the legal and institutional framework, explanations of specific,...